2018
DOI: 10.18632/oncotarget.25166
|View full text |Cite
|
Sign up to set email alerts
|

Biological and metabolic effects of IACS-010759, an OxPhos inhibitor, on chronic lymphocytic leukemia cells

Abstract: Blood cells from patients with chronic lymphocytic leukemia (CLL) are replicationally quiescent but transcriptionally, translationally, and metabolically active. Recently, we demonstrated that oxidative phosphorylation (OxPhos) is a predominant pathway in CLL for energy production and is further augmented in the presence of the stromal microenvironment. Importantly, CLL cells from patients with poor prognostic markers showed increased OxPhos. From these data, we theorized that OxPhos can be targeted to treat C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 40 publications
1
40
0
Order By: Relevance
“…Interestingly, both IACS/VIN and RT/2-DG combinations significantly enhanced ECAR (extracellular acidification rate) by 27-234% in MOLM-13 cells and studied patient samples (n = 5/6), as well as in PBMCs in case of IACS/VIN (Table S8). Previous reports have shown that inhibiting Complex I of the ETC with IACS-010759 or rotenone upregulates glucose consumption and glycolysis (42,43). As expected, normalized coupling efficiency was also significantly associated (r = 0.786, p < 0.001) with ATP-linked OCR ( Figure 7E).…”
Section: Iacs-010759/vinorelbine and Rotenone/2-deoxy-d-glucose Combisupporting
confidence: 82%
See 1 more Smart Citation
“…Interestingly, both IACS/VIN and RT/2-DG combinations significantly enhanced ECAR (extracellular acidification rate) by 27-234% in MOLM-13 cells and studied patient samples (n = 5/6), as well as in PBMCs in case of IACS/VIN (Table S8). Previous reports have shown that inhibiting Complex I of the ETC with IACS-010759 or rotenone upregulates glucose consumption and glycolysis (42,43). As expected, normalized coupling efficiency was also significantly associated (r = 0.786, p < 0.001) with ATP-linked OCR ( Figure 7E).…”
Section: Iacs-010759/vinorelbine and Rotenone/2-deoxy-d-glucose Combisupporting
confidence: 82%
“…IACS-010759, which is currently in clinical development, is a novel OxPhos inhibitor that targets mitochondrial complex I (35). This compound caused only minor cell death of chronic lymphocytic leukemia at 24 h of treatment, but the addition of 2-deoxy-D-glucose significantly increased cytotoxicity (43). Here we demonstrate that the combination of IACS-010759 and vinorelbine impairs several mitochondrial functions, such as oxygen consumption and coupling efficiency.…”
Section: Discussionmentioning
confidence: 71%
“…At present, the prevailing plasticity of the metabolic circuitry is thought to be the greatest limiting factor in the success of metabolic inhibition, rendering the singular targeting of metabolic pathways ineffective. Dual metabolic inhibition is a promising strategy to overcome this, especially combinations involving the inhibition of glycolysis and OXPHOS, or glycolysis and glutaminolysis [ 185 , 223 , 230 , 231 , 233 ]. Though supported by robust preclinical data, the clinical evaluation of dual metabolic inhibitor strategies remain in their infancy stages [ 286 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another complex I inhibitor, IACS-010759, recently demonstrated preclinical efficacy in inhibiting growth of CLL and acute myeloid leukaemia (AML) [ 185 ]. IACS-010759 is potent and can be administered orally, and has progressed to phase I trials in advanced solid tumours, which was reported to be well-tolerated with preliminary evidence of anti-tumour activity.…”
Section: Therapeutic Opportunities Targeting Altered Ccmmentioning
confidence: 99%
See 1 more Smart Citation